2014
DOI: 10.1002/oby.20855
|View full text |Cite
|
Sign up to set email alerts
|

Stability and changes in metabolically healthy overweight or obesity and risk of future diabetes: Niigata wellness study

Abstract: Objective: Stability and changes in obesity and metabolic health status from a baseline period and longitudinally investigated their impact on predicting future diabetes were assessed. Methods: Studied were 27,478 Japanese individuals without diabetes. Metabolically healthy (MH) was indicated by having 1 among impaired fasting glucose, hypertension, hypertriglyceridemia and low HDL cholesterol concentration. Metabolically abnormal (MA) was indicated by having 2 of those metabolic abnormalities. A cut-off value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 32 publications
4
45
0
Order By: Relevance
“…This result confirms other studies (7, 8, 9, 10) and suggests that “metabolically healthy” obesity is a misnomer as it is still associated with increased risk for hypertension and DM. Second, our study documented that hyperuricemia is an independent risk factor for developing hypertension and DM in the overall population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result confirms other studies (7, 8, 9, 10) and suggests that “metabolically healthy” obesity is a misnomer as it is still associated with increased risk for hypertension and DM. Second, our study documented that hyperuricemia is an independent risk factor for developing hypertension and DM in the overall population.…”
Section: Discussionsupporting
confidence: 91%
“…While obesity is recognized as an independent risk factor for hypertension and diabetes mellitus (DM) (7, 8, 9, 10), the classical approach in obesity research is to control for the various metabolic risk factors, many of which may be causally linked to obesity. An alternative approach would be to perform longitudinal analyses in which subjects with obesity are stratified at baseline into those with or without metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…MHO class II without any metabolic abnormality did not significantly increase the risk of CACS progression even after adjusting for possible confounders. By contrast, MHO class I, which has been frequently defined in previous studies [2427,29,30], showed a 1.7-fold higher risk for CACS progression than non-obese metabolically healthy subjects. A stratified analysis of this MHO class I group according to the number of metabolic abnormality (that is, 0 or 1) showed that there was a significant difference in the risk of CACS progression between MHO subjects with no metabolic abnormality and one metabolic abnormality at the baseline.…”
Section: Discussionmentioning
confidence: 78%
“…Briefly, obese participants who met ≤ 1 of the following National Cholesterol Education Program–Adult Treatment Panel III (NCEP–ATP III) criteria for metabolic syndrome [28] were considered to have MHO class I: (a) TG level ≥ 1.7 mmol/L (150 mg/dL); (b) HDL cholesterol level < 1.0 mmol/L (40 mg/dL) in men and < 1.3 mmol/L (50 mg/dL) in women; (c) blood pressure ≥ 130/85 mmHg or intake of antihypertensive medication; and (d) fasting glucose level ≥ 5.6 mmol/L (100 mg/dL) or intake of anti-diabetic medication. The WC criterion was not used in the definition of metabolic health as in the previous studies [2427,29,30], because of collinearity with BMI. Additionally, we defined MHO using stricter criteria following the Healthy Obese Project, which was a population-based cohort study conducted in 7 European countries (MHO class II) [31]: MHO class II was established when subjects with obesity had none of the metabolic syndrome components.…”
Section: Methodsmentioning
confidence: 99%
“…This was a cross-sectional study, so it was not possible to determine the cause-effect relationship between serum zinc level and metabolic health status. Furthermore, metabolic health profiles such as MONW and MHO are dynamic conditions, and changes in BMI and metabolic condition result in different metabolic outcomes [40]. Further longitudinal follow-up studies of the relationship between serum zinc and changes in metabolic health status are now needed.…”
Section: Article In Pressmentioning
confidence: 99%